(untitled) (Research, Society and Development, 2020)
In oil industry, oil emulsions are recurring problems and them can be oil in water (A / O) or water in oil (A/O) type. An alternative currently studied for breaking emulsions is the use of Microemulsionated Systems (MS) that have the characteristic of solubilizing polar and nonpolar substances. The objective of this work was the synthesis of a surfactant from a vegetable oil, as well as the formulation of microemulsion for breaking emulsions of type A/O. For the synthesis of the surfactant, Moringa Oleifera Lam oil was saponified and characterized by Saponification Index and Hydrophilic-Lipophilic Balance. The microemulsion systems were formulated using Saponified Moringa Oil as Surfactant (S), n-butanol as cotensoactive (C), moringa oil as oily phase and distilled water as aqueous phase and the ratio C/S was varied at 1, 5 and 10. To validate the results of emulsion break the Scheffé’s network was employed. The oil was characterized according to ABNT NBR 14647 and had a BSW (Basic Sediments and Water) content of 24%. The results showed at the end of the experiments of 30 minutes an aqueous phase separation efficiency of 40%. Furthermore, it was found that the relationship between the microemulsion concentration and the separation percentage is not linear, and the biggest gain in the separation efficiency occurs for lower concentrations (about 8%). Therefore, the study made it possible to investigate the capacity of microemulsion systems developed to break A/O emulsions, as well as to optimize the microemulsion concentration to be used in the process.